DNA links Andean tepui endemic Helonoma peruviana to Hapalorchis (Orchidaceae, Spiranthinae) - Salazar, Gerardo A.; Baquero, Luis; Jiménez, Marco; Rizo-Patrón, Federico (Phytotaxa, 2022)
Helonoma peruviana is here reported as a generic and specific addition to the Ecuadorian orchid flora based on a plant found recently in the Cordillera del Cóndor. The systematic position of H. peruviana was assessed by means of a Bayesian inference analysis of plastid (matK-trnK, trnL-trnF) and nuclear (ITS) DNA sequences from 43 genera and 50 species of Spiranthinae, plus suitable outgroups. The analysis recovered H. peruviana as the strongly supported sister of Hapalorchis, being more distantly related to Beloglottis, a genus in which Helonoma has been merged at the sectional level. Despite some differences in perianth morphology, Helonoma and Hapalorchis share both vegetative (densely pubescent roots, decumbent rhizome) and reproductive traits (similar column and pollinarium morphology). Helonoma has a disjunct distribution between the Guiana Shield and the Andean tepui region, and H. peruviana is restricted to the later in Colombia, Ecuador, and Peru.